2014
DOI: 10.1080/21553769.2014.924080
|View full text |Cite
|
Sign up to set email alerts
|

In vitrostudy on cytotoxic effect and anti-DENV2 activity ofCarica papayaL. leaf

Abstract: Dengue fever is the most deleterious and rapidly spreading mosquito-borne viral disease, and to date it has resisted attempts to eradicate it. Carica papaya L. leaf extract is traditionally used to cure dengue fever and its associated symptoms. However, no in vitro studies have been reported for the anti-dengue efficacy of this extract. So, the present study attempted to determine the phytochemicals present in Carica papaya L. leaf extracts, as well as their cytotoxic effect and anti-DENV2 activity on the LLC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…However, drowsiness in doses between 1200 and 5000 mg/kg was reported [ 77 ] The compounds isolated from the methanol stem bark fraction (resveratrol derivatives) were reported to have low cytotoxicity on prostate cancer cell lines [ 78 ]. The ethanol root extract was reported to be nontoxic in brine shrimp larvae [ 74 ] Warburgia salutaris (G.Bertol) Chiov Chest complaints, cough, fever, pneumonia [ 79 ], yellow fever [ 80 ], common cold, malaria [ 81 ], Aspergillosis [ 82 ] Fungicidal activity against Fusarium species (Acetone extract) [ 83 ] antimycobacterial activity against S. aureus, B. subtilis, S. epidermis, M. luteus, E. coli, and K. pneumoniae ) [ 84 ] in vitro (Hole plate diffusion method, microdilution method) [ 83 ], in vitro (Bioautography assay) [ 84 ] The acetone leaf extract was reported to be cytotoxic against cancer cell lines [ 85 ] Carica papaya L. Malaria, liver disease [ 12 ], tuberculosis [ 30 ], malaria, [ 86 , 87 ], fever [ 18 ] Antibacterial activity (Methanol root extract) [ 88 ], antitumour activity and immunomodulatory effects (Aqueous leaf extract) [ 89 ] in vitro (Cup plate agar diffusion method) [ 88 ], in vitro (Cell viability assay, caspase assay, microarray analysis) [ 89 ] The aqueous and ethanol leaf extracts were reported to be cytotoxic on human oral squamous cell carcinoma SCC25 cell lines [ 90 ] The aqueous leaf extract was reported to disrupt cell division and to induce mitotic spindle disturbance in Allium cepa [ 91 ] The methanol leaf extract was reported to be cytotoxic against LLC-MK2 cell lines [ 92 ] The aqueous leaf extract was reported to be non-toxic in Sprague Dawley rats at a 2000 mg/kg dose [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, drowsiness in doses between 1200 and 5000 mg/kg was reported [ 77 ] The compounds isolated from the methanol stem bark fraction (resveratrol derivatives) were reported to have low cytotoxicity on prostate cancer cell lines [ 78 ]. The ethanol root extract was reported to be nontoxic in brine shrimp larvae [ 74 ] Warburgia salutaris (G.Bertol) Chiov Chest complaints, cough, fever, pneumonia [ 79 ], yellow fever [ 80 ], common cold, malaria [ 81 ], Aspergillosis [ 82 ] Fungicidal activity against Fusarium species (Acetone extract) [ 83 ] antimycobacterial activity against S. aureus, B. subtilis, S. epidermis, M. luteus, E. coli, and K. pneumoniae ) [ 84 ] in vitro (Hole plate diffusion method, microdilution method) [ 83 ], in vitro (Bioautography assay) [ 84 ] The acetone leaf extract was reported to be cytotoxic against cancer cell lines [ 85 ] Carica papaya L. Malaria, liver disease [ 12 ], tuberculosis [ 30 ], malaria, [ 86 , 87 ], fever [ 18 ] Antibacterial activity (Methanol root extract) [ 88 ], antitumour activity and immunomodulatory effects (Aqueous leaf extract) [ 89 ] in vitro (Cup plate agar diffusion method) [ 88 ], in vitro (Cell viability assay, caspase assay, microarray analysis) [ 89 ] The aqueous and ethanol leaf extracts were reported to be cytotoxic on human oral squamous cell carcinoma SCC25 cell lines [ 90 ] The aqueous leaf extract was reported to disrupt cell division and to induce mitotic spindle disturbance in Allium cepa [ 91 ] The methanol leaf extract was reported to be cytotoxic against LLC-MK2 cell lines [ 92 ] The aqueous leaf extract was reported to be non-toxic in Sprague Dawley rats at a 2000 mg/kg dose [ …”
Section: Resultsmentioning
confidence: 99%
“…Malaria, liver disease [12], tuberculosis [30], malaria, [86,87], fever [18] Antibacterial activity (Methanol root extract) [88], antitumour activity and immunomodulatory effects (Aqueous leaf extract) [89] in vitro (Cup plate agar diffusion method) [88], in vitro (Cell viability assay, caspase assay, microarray analysis) [89] The aqueous and ethanol leaf extracts were reported to be cytotoxic on human oral squamous cell carcinoma SCC25 cell lines [90] The aqueous leaf extract was reported to disrupt cell division and to induce mitotic spindle disturbance in Allium cepa [91] The methanol leaf extract was reported to be cytotoxic against LLC-MK2 cell lines [92] The aqueous leaf extract was reported to be non-toxic in Sprague Dawley rats at a 2000 mg/kg dose [93] No morphological alterations were reported in Sprague Dawley rats treated with a 28-day repeated oral dose of 2000 mg/kg [94] Aqueous and ethanol leaf extracts were reported to be nontoxic at doses of up to 5000 mg/kg [95] The methanol leaf, root, and stem bark extracts were reported to be nontoxic against MRC- 5 Croton megalocarpus Del.…”
Section: Diversity Of Medicinal Plants Identified In the Study Area Amentioning
confidence: 99%
“…Fresh leaves are used to cure gastrointestinal problems and hepatic disease and it also acts as anti-inflammatory and natural abortion agent. In India, traditional Siddha medicinal systems prescribe C. papaya L leaf extract to patients with dengue fever symptoms [43].  Daily consumption of leaves helps to prevent malaria in Indonesia, aqueous extracts of papaya leaves consumption also increases platelets WBC and neutrophils counts ( especially in dengue patients).…”
mentioning
confidence: 99%
“…In vitro antiviral activity of Irvingia gabonensis extract against human immunodeficiency virus (HIV) has been reported (Abdurahman et al, 1995). In vitro and pilot study have reported antiviral activity of Carica papaya leaves aqueous extract against dengue virus (Sathyapalan et al, 2020;Sharma et al, 2019;Joseph et al, 2015), through inhibition of the viral non-structural 2B and 3 (NS2B-NS3) protease complex which is crucial for virus replication (Senthilvel et al, 2013) and this is similar to the mechanism reported for simeprevir (Verbinnen et al, 2015) and clemizole (Einav et al, 2008). Carica papaya and Corchorus olitorius have been used to treat asthma properties in Nigerian traditional medicine (Erinoso & Aworinde, 2012).…”
Section: Discussionmentioning
confidence: 99%